2021
DOI: 10.1002/jcp.30532
|View full text |Cite
|
Sign up to set email alerts
|

Nampt affects mitochondrial function in aged oocytes by mediating the downstream effector FoxO3a

Abstract: Maternal aging can impair the quality and decrease the developmental competence of ovulated oocytes. In this study, compromised germinal vesicle breakdown (GVBD) was found in aged mice oocytes. Furthermore, we observed increased reactive oxygen species (ROS) and mitochondrial Ca2+ levels, along with reduced mitochondrial temperature in aged oocytes. Maternal aging also changed the crotonylation level in oocytes. Forkhead box O3 (FoxO3a), a member of the forkhead protein family involved in the regulation of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…In agreement with our previous findings, the GVBD rate was significantly decreased in the aged oocytes, while the PBE rate was similar (16). As we pointed out in our previous report, aged oocytes underwent both GVBD and PBE more slowly than young oocytes, this indicated that the meiotic process in the aged oocytes was disrupted to a certain extent (16). In the present study, we found PCB2 supplementation can significantly improve the GVBD rate in aged oocytes (Figure 1).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previous findings, the GVBD rate was significantly decreased in the aged oocytes, while the PBE rate was similar (16). As we pointed out in our previous report, aged oocytes underwent both GVBD and PBE more slowly than young oocytes, this indicated that the meiotic process in the aged oocytes was disrupted to a certain extent (16). In the present study, we found PCB2 supplementation can significantly improve the GVBD rate in aged oocytes (Figure 1).…”
Section: Discussionsupporting
confidence: 93%
“…We previously found that 5 µg/mLPCB2 supplementation during in vitro maturation progress could attenuate meiosis defects, improve the subsequent developmental potential after parthenogenetic activation of diabetic mouse oocytes (12). In agreement with our previous findings, the GVBD rate was significantly decreased in the aged oocytes, while the PBE rate was similar (16). As we pointed out in our previous report, aged oocytes underwent both GVBD and PBE more slowly than young oocytes, this indicated that the meiotic process in the aged oocytes was disrupted to a certain extent (16).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In older oocytes, in addition to increased concentrations of reactive oxygen species, mitochondrial damage, increased meiotic errors, autophagy, and premature apoptosis are noted [ 11 , 56 ]. In addition to reduced oocyte quality, excessive aging can lead to slower passage through the developmental phases, as indicated in pigs [ 57 ]. SIRT1 is a protein whose activity is strongly associated with states of elevated concentrations of reactive oxygen species and has been proven to mitigate oocyte aging [ 58 ], and loss of SIRT1 causes increased oocyte aging [ 59 ].…”
Section: Sirt1 and Agingmentioning
confidence: 99%
“…Obese, diabetic, and aging women having lower rate of oocyte activation, altered preimplantation embryo development, and even lower pregnancy rates have been highlighted [26][27][28][29], and these disorders have been related to the mitochondrial dysfunction in oocytes [5], because the ATP production and oxidative phosphorylation are essential for reproductive cellular processes including meiotic maturation and postimplantation development [30]. Our previous stud- We further found that the spindle/chromosome structure was damaged in drug-treated MII oocytes (Figures 2(a)-2(d)), indicating that oocytes are in poor quality, also supporting our previous studies that the depletion of MCU markedly disrupts spindle formation during oocyte meiosis [10].…”
Section: Discussionmentioning
confidence: 99%